Students Ability in Analysis Simple Past Tense Errors in Recount Text in The Eighth Grade Students of SMP Negeri 15 Padang - Immana Rizki; Dian Safitri (Universitas Negeri Padang, 2023)
In curriculum, students in junior high school were asked to write a variety of text. The recount text was one of those. Meanwhile, Based on previous research, there are still many students who make errors in using the simple past tense when compiling English texts, especially in writing recount texts and the types of errors are omission, addition, misformation, and misordering. Purpose of this research were To know the ability of eighth grade students of SMP Negeri 15 Padang in analyzing errors contained in recount text. The researcher conducts a descriptive study. the result of 70 samples, the total score was 693. The highest score that the students got was 100 (student 58) and lowest score was 25 (student 36). The text by student 58 was good based on the five aspects (the highest score). It was proved that in all aspects the students were in good to excellent ability level. Meanwhile, the student 36 got the lowest score because he does not know what is the error.